Strategy-proof and anonymous allocation rules of indivisible goods: A new characterization of Vickrey allocation rule - Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2006)
We consider situations where a society allocates a finite units of an indivisible good among agents, and each agent receives at most one unit of the good. For example, imagine that a government allocates a fixed number of licences to private firms, or imagine that a government distributes equally divided lands to households. We show that the Vickrey allocation rule is the unique allocation rule satisfying strategy-proofness, anonymity and individual rationality.
Keywords: 330; strategy-proofness; anonymity; indivisible good; Vickrey allocation rule